Development of a diagnosing system for the absorption-distillation department of soda ash production - Pereverzieva, Alevtyna; Bobukh, Anatoly; Podustov, Mikhail (Технологический центр, 2020)
Production of soda ash using the ammonia method belongs to the class of complex continuous chemical-technological systems and is characterized by multidimensionality, inertia, the existence of cycles of material flows, complex dependences between the input and output parameters of technological modes. The research into the operation of this production and its performance indicators revealed that 24–26 % of losses in soda ash production were caused by violations of the technological mode at the absorption-distillation department. Many of these violations can be prevented, and losses can be significantly reduced, by developing a system of diagnosing the state of technological processes at this department. The main task of the diagnosing system at the absorption-distillation department is to determine the moment of transition of the technological process to the emergency state, disabling the control system, informing a technologist-operator about the probable cause of the emergency, and giving recommendations for its elimination. After the elimination of the reasons for the deviation of the technological process from normal functioning, the measures on switching on the control system are taken. The system of diagnosing an absorption-distillation department of soda ash production should be implemented based on the passive observations of the course of the technological process. This is due to the continuity of production, on the one hand, and the requirement to adhere to the mode of the normal functioning of the technological process, on the other hand. The results of the analysis of diagnosing emergencies prove that the implementation of the method of logical decision tables will enhance the speed of the diagnosing process and improve its quality due to the prevention and timely liquidation of emergencies. It was established that if the same emergency analysis vector corresponds to different causes of emergencies in this system, it is necessary to use characteristics of the statistical theory of solutions.

Виробництво кальцинованої соди аміачним способом відноситься до класу складних неперервних хіміко-технологічних систем та характеризується багатомірністю, інерційністю, наявністю циклів матеріальних потоків, складними залежностями між вхідними і вихідними параметрами технологічних режимів. Дослідження роботи цього виробництва та показників його роботи показали, що 24–26 % втрат за випуском кальцинованої соди відбулися із-за порушень технологічного режиму відділення абсорбції-дистиляції. При цьому багато з цих порушень можна попередити, а втрати значно зменшити за рахунок розробки системи діагностики стану технологічних процесів цього відділення. Основною задачею системи діагностики відділення абсорбції-дистиляції є визначення моменту переходу технологічного процесу в аварійний стан, відключення системи управління, повідомлення технологу-оператору про ймовірну причину аварійної ситуації та рекомендації по її усуненню. Після усунення причин відхилення технологічного процесу від нормального функціонування передбачені заходи по включенню системи управління. Система діагностики відділення абсорбції-дистиляції виробництва кальциновано соди повинна бути реалізована на основі пасивних спостережень за ходом технологічного процесу. Це обумовлено безперервністю виробництва, з одного боку, та вимогою дотримання режиму нормального функціонування технологічного процесу, з другого боку. За результатами аналізу діагностики аварійних ситуацій підтверджується, що реалізація методу логічних таблиць рішень буде сприяти підвищенню швидкості процесу діагностики та покращанню його якості за рахунок попередження та своєчасної ліквідації аварійних ситуацій. Встановлено, якщо одному і тому вектору аналізу аварійних ситуацій відповідають різні причини аварійних ситуацій цієї системи необхідно використовувати характеристики статистичної теорії рішень.
Розробка системи діагностики відділення абсорбції-дистиляції виробництва кальцинованої соди
Keywords: soda ash; diagnosing system; logical decision tables; analysis vector; кальцинована сода; система діагностики; логічні таблиці рішень; вектор аналізу